GE_GERICHTE P/687/2017 vom 11. September 2019 - GE Cour de justice (2019)
LÉSION CORPORELLE;PARTIE CIVILE;TORT MORAL;POUVOIR D'EXAMEN LIMITÉ;DÉFENSE D'OFFICE | CP.123.al1; CPP.391.al1.letB; CPP.398.al5; CPP.122.al1; CO.47; CPP.135